Design of Wireless Devices for Conventional Projector - Yusman Fauzan (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2016)
At this wireless device functions to allow users to connect a computer or laptop to the projector. Typically users are still using a connecting cable between the computer or laptop to the projector. The use of this wireless device has a wide outreach to users. The use of wireless devices can be used in open spaces. The range that can be accessed by the user up to 20 meters. In using this wireless device users need to install the driver software to be used. The software serves as a command in order to connect to the wireless device as expected. If the user wants to connect to a wireless device must have Wi-Fi on your computer or laptop. The wireless device consists of a Wi-Fi module type TP-LINK TL-WN832N and Raspberry Pi mini PC that Rev. B +. Wi-Fi module type TP-LINK TL-WN832N serves to make the Access Point (AP) network that can be accessed by users. Mini PC serves as the command-processing performed by the user. The use of the user's overall access via Wi-Fi module with a security key in it, then open a browser to connect to it. Expected when using the average speed of data transmission is 1.43 MB/s and the total data 7.22 MB. In the use of wireless devices is the second that will appear on the projector screen.